2017
DOI: 10.4172/2329-888x.1000173
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Hand-Held Meter to Detect Subclinical Ketosis in Dairy Cows

Abstract: The objective of this study was to evaluate the performance of a new cowside test in detecting sub-clinical ketosis (SCK) by comparing β-hydroxybutyrate (BHBA) concentrations obtained using a new hand-held meter, TNN (Yicheng Co., Beijing, China), with those obtained from the conventional laboratory method and to compare the accuracy of using blood, urine and milk samples for diagnostic purposes. TNN is based on an enzymatic electrochemical technique to detect SCK in dairy cows. 297 samples of blood, 97 sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(43 reference statements)
1
2
0
1
Order By: Relevance
“…The average increase of milk yield at the raised indoor temperature was 0.284 kg day −1• C −1 in this study. Xu et al [17] indicated that milk production of dairy cows at the peak of lactation decreased by 0.365 kg day −1 as the rearing temperature dropped by 1 • C. This is reasonable since the lactation periods were mixed in the experimental group of this study. The milk production response of cows in the early lactation could be less sensitive than the cows in the peak lactation period.…”
Section: Variablesupporting
confidence: 68%
See 1 more Smart Citation
“…The average increase of milk yield at the raised indoor temperature was 0.284 kg day −1• C −1 in this study. Xu et al [17] indicated that milk production of dairy cows at the peak of lactation decreased by 0.365 kg day −1 as the rearing temperature dropped by 1 • C. This is reasonable since the lactation periods were mixed in the experimental group of this study. The milk production response of cows in the early lactation could be less sensitive than the cows in the peak lactation period.…”
Section: Variablesupporting
confidence: 68%
“…During this period, the suitability of the ambient environment affects the production level of dairy cows. Xu et al identified the temperature drop period when the average temperature decreased by more than 5 • C within 3 days, which would significantly reduce dry matter intake and milk production of cows in early lactation and peak lactation [17]. Lim et al found that the milk yield was improved by adding LED lights during the photoperiod of 16 h [18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, portable ketone measuring devices offer an alternative to laboratory tests and allow quick and reliable measurements to be obtained at a relatively low cost and with little blood. The devices have already been used in the case of domestic animals such as sheep or dairy cows ( Hornig et al , 2013 ; Geishauser et al , 2001 ; Iwersen et al ., 2013 ; Xu et al , 2017 ) and have also been used successfully in wild bat species ( Boyles et al , 2016 ). However, portable devices have rarely been used to measure ketones in wild birds and we are only aware of three studies so far ( Azeredo et al , 2016 ; Sommers et al , 2017 ; Lindholm et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Esta condición puede afectar negativamente la salud del animal, por la presentación de signos clínicos de cetosis y por la asociación que esta tiene con enfermedades puerperales, como desplazamiento de abomaso, metritis y claudicaciones (Duffield et al 2009). Se ha observado también, que en animales con cetosis subclínica, la producción de leche disminuye significativamente (Xu et al 2017, Antanaitis et al 2018. El β-hidroxibutirato (βHB), uno de los cuerpos cetónicos, se usa para diagnosticar esta condición, por ser el más predominante y estable en la leche, la orina y el suero En condiciones fisiológicas normales, se producen cuerpos cetónicos, que son los que proveen de energía a los tejidos extrahepáticos y su concentración no debe superar 1.2 mmol/Lt, en sangre o 0.15 mmol/ Lt, en leche (Duffield et al 2009;Chandler et al 2017).…”
Section: Introductionunclassified